Antecedents Varıables of Intentıon to Use Servıce Innovatıon: An Empırıcal Study of E-Toll Card - Aldio Pramudya Gunadi; Sabrina O Sihombing (Department of Management, Faculty of Economics and Business, Brawijaya University, 2013)
Lack of consumer willingness to adopt electronic toll card in Jakarta triger the congestion at the toll gates. This congestion has been one of the critical factors that needs to be more focused by PT Jasa Marga as highway toll service company. The fact shows that only 5.88% of all the total transactions in the toll gates applied E-toll card facility. These facts provide evidence about the lack of consumer willingness to adopt E-Toll card. Therefore, the understanding of consumer behavior to adopt sevice innovation is necessary to solve these lack of consumer unwillingness. This study was developed by replicated the research of Lee (2012) that reveal the antecedents factors that affect the consumer intention to adopt service innovation. Respondents of this research were 217 students from a private university in Tangerang. Respondent were collected by using judgemental sampling based on their experience in using E-toll card. The survey instrument employed demographic background, consumer attitude, perceived ease of use, perceived price fairness, satisfaction with existing service, fashion consciousness, risk averseness and consumer intention to adopt service innovation. Structural equation modeling (SEM) was applied to analyze the data. Result indicated that consumer attitude, perceived ease of use, satisfaction with existing service, risk averseness, and fashion consciousness are the predictors of consumer intention to adopt service innovation. This research also provides the theoretical implication, managerial implication, and suggestion for future research.